Pengembangan media storybook pic-pop berbasis budaya lokal Palembang untuk meningkatkan perilaku prososial anak usia dini - Ade Tria Lestari; Hapidin Hapidin; Zarina Akbar (Universitas Muhammadiyah Ponorogo, 2020)
Important aspects of social-emotional development developed in early childhood, specifically about prosocial habits. This study aims to develop a book about Palembang's local culture to improve understanding of prosocial behaviour in early childhood. Draw local culture through interesting pictures. The research method used is research and development with the ADDIE model. The technique of collecting data is based on the results of expert validation and trial data through pre-trial one group pretest-posttest design and statistical analysis of data using paired sample t-test. This study involved children aged 4 to 6 years in Musi Banyuasin Regency. The product research and development results show: first, the design of storybook media product is feasible to increase children's understanding of Palembang's cultural and prosocial behaviour; second, collecting media that is seen from the results obtained from the pretest-posttest data of children with a value and significance of 0.00 0.05, this shows the value of the pretest-posttest supports the difference; and third, the validity of the media that shows the book can be used for children who understand cultural literacy so that children are rich in cultural insights specifically the local culture of Palembang.